2007
DOI: 10.1002/asi.20562
|View full text |Cite
|
Sign up to set email alerts
|

Understanding student information behavior in relation to electronic information services: Lessons from longitudinal monitoring and evaluation, Part 2

Abstract: This second part of a two-part article establishes a model of the mediating factors that influence student information behavior concerning the electronic or digital information sources used to support learning. This part discusses the findings of the Joint Information Systems Committee User Behavior Monitoring and Evaluation Framework (1999)(2000)(2001)(2002)(2003)(2004) and development of a model that includes both the individual (micro) and organizational (macro) factors affecting student information behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 29 publications
1
57
1
Order By: Relevance
“…For the purpose of this article, information seeking behaviour is defined as what takes place when an individual (or group) identifies an information gap and purposefully tries to fill it; whilst information searching includes the physical acts of looking for information. Logically, studies of information seeking may include elements of searching as indicated in Wilson's (1999) nested model.From the data obtained from a longitudinal study of the use of electronic information services among academic staff and students in the UK, a model was derived of the mediating factors that influenced student use of electronic information services (in particular) (Urquhart and Rowley, 2007). This model embraced not just the factors associated with individuals but some of the contextual factors as well.…”
mentioning
confidence: 99%
“…For the purpose of this article, information seeking behaviour is defined as what takes place when an individual (or group) identifies an information gap and purposefully tries to fill it; whilst information searching includes the physical acts of looking for information. Logically, studies of information seeking may include elements of searching as indicated in Wilson's (1999) nested model.From the data obtained from a longitudinal study of the use of electronic information services among academic staff and students in the UK, a model was derived of the mediating factors that influenced student use of electronic information services (in particular) (Urquhart and Rowley, 2007). This model embraced not just the factors associated with individuals but some of the contextual factors as well.…”
mentioning
confidence: 99%
“…Logically, studies of information seeking may include elements of searching as indicated in Wilson's (1999) nested model. Student information seeking has often been described in terms of comfort or convenience (MacDonald et al (2011); Prabha et al (2007) ; Zach (2005).Models of information seeking behaviour among students include a model of the mediating factors that influenced student use of electronic information services (in particular) (Urquhart and Rowley, 2007). The specific (micro) factors were information literacy (defined in terms of skills and knowledge that students could bring to searching), searching strategies (the type of searching routines normally adopted), academics' information behaviour (and their influence as role models for students), discipline, pedagogy (approach adopted to learning and teaching), and support and training (provided partly by library services, perhaps acting in co-operation with academic staff).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For those who teach searching, understanding how students search for online information is an important aspect. In their Information Behavior Model, Urquhart and Rowley (2007) identified many micro and macro factors that impact student information behaviours, including information literacy, search strategies, discipline and curriculum, pedagogy, support and training, information resource design, and access. Many students typically begin searching with Google (Griffiths & Brophy, 2005;Urquhart & Rowley, 2007), relying less on academic resources (Griffiths & Brophy, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In their Information Behavior Model, Urquhart and Rowley (2007) identified many micro and macro factors that impact student information behaviours, including information literacy, search strategies, discipline and curriculum, pedagogy, support and training, information resource design, and access. Many students typically begin searching with Google (Griffiths & Brophy, 2005;Urquhart & Rowley, 2007), relying less on academic resources (Griffiths & Brophy, 2005). Starting searches with Google and limiting use of resources to those that are well known is typical, as ease of use and familiarity are important factors in their choice of resource (Dervin & Reinhard, 2007;Griffiths & Brophy, 2005;Urquhart & Rowley, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation